Conversion of the chemical concentration of odorous mixtures into odour concentration and odour intensity: A comparison of methods. (February 2016) - Wu, Chuandong; Liu, Jiemin; Zhao, Peng; Piringer, Martin; Schauberger, Günther
Abstract: Continuous odour measurements both of emissions as well as ambient concentrations are seldom realised, mainly because of their high costs. They are therefore often substituted by concentration measurements of odorous substances. Then a conversion of the chemical concentrations C (mg m −3 ) into odour concentrations C OD (ouE m −3 ) and odour intensities OI is necessary. Four methods to convert the concentrations of single substances to the odour concentrations and odour intensities of an odorous mixture are investigated: (1) direct use of measured concentrations, (2) the sum of the odour activity value SOAV, (3) the sum of the odour intensities SOI, and (4) the equivalent odour concentration EOC, as a new method. The methods are evaluated with olfactometric measurements of seven substances as well as their mixtures. The results indicate that the SOI and EOC conversion methods deliver reliable values. These methods use not only the odour threshold concentration but also the slope of the Weber–Fechner law to include the sensitivity of the odour perception of the individual substances. They fulfil the criteria of an objective conversion without the need of a further calibration by additional olfactometric measurements. Graphical abstract: Highlights: Concentration of odorous substances as surrogate for odour concentration/intensity. Comparison of conversion methods with various degrees of complexity. Model evaluation by seven VOCs: 23 binary mixtures and 5 mixtures of 7 substances. Model input: odour threshold concentration and the slope of the Weber–Fechner law. No further calibration by olfactometric measurements necessary.